Juvenile Social Media Hate Crime and Community Safety: Indonesia’s Constitutional Overview and Restorative Justice Challenges - Abdurrakhman Alhakim; Eko Nurisman; Tantimin Tantimin (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This study aims to analyze the emerging juvenile criminal trend within social media usage. Utilizing normative legal research method, this study focuses on the potentials and challenges of employing restorative justice for juvenile hate crime offenders. Analysis supported by statutory approach found that Indonesia normatively supports youth development but doesn’t specifically connect the restorative justice approach with the concept of community safety. Through the statutory approach, this study also found that there’s no recognition on the different nature of hate crimes, especially among youth, which could have different and unique negative effects on community safety. These findings serve the purpose of expanding the literature and providing deeper insights for the development of legal framework to support the application of restorative justice approach in Indonesia, by expanding it to include concept of community safety.